CONTRIBUIÇÃO DA GOVERNANÇA DE REDES DE STAKEHOLDERS PARA O DESENVOLVIMENTO REGIONAL SUSTENTÁVEL: ESTUDO DE CASO SOBRE O CEAP AMAZÔNIA - Garbelini, Gislaine (2009)
The aim of this study was to analyze stakeholders network governance policies and practices designed to promote regional sustainable development. Given the necessary involvement of different stakeholders in economic, environmental and social fields in order to obtain a more balanced and fairer society, a lack of stakeholder engagement in the organizational sphere may hinder the implementation of a stakeholder governance model that promotes sustainable development. In order to investigate this assumption, Petrobras Environmental Center of Excellence (Ceap Amazônia) was used as a case study. Most recent studies about stakeholder networks focus on investigating the transactional results that they may produce, rather than the transformational results that generate values capable of contributing to sustainability on an organizational and regional level. This is a qualitative and exploratory study, involving bibliographic, documental and field research. The study concludes that traditional methods of corporate governance have not been effective in achieving complex goals such as regional sustainable development. Hence the need to establish new models of governance that involve stakeholders engagement aligned with sustainability values. The theoretical framework is based on the following themes: stakeholder theory, networks, corporate governance and sustainability indicators. These themes support the conceptual analytical model known as the GovRedeS model used in the case study. Its application showed new aspects that have been incorporated into a revised version of the GovRedeS. The model was shown to be appropriate and consistent in investigating the Ceap Amazônia network, and may be used for other investigations, considering that necessary adjustments should be made to the organizational structures and cultures of each network and their political, cultural, environmental and social environment.